Bacterial Infections and Relevant Factors in Neonates Hospitalized at Intensive Care Unit - Milad Kabiri Samani; Majid keivanfar; Hossein Firouzi; Seyed Javad Seyedi; Hamidreza Kianifar (Mashhad University of Medical Sciences, 2019)
Background: Among the most common causes of death in preterm infants are neonatal infections, which remain high despite antibiotic therapy and preservative measures. The control of hospital infections is now a global priority, and many factors contribute to the spread of these infections. This study aimed to determine the frequency of bacterial infections in neonates and identify the common causes of infection in neonates admitted to the neonatal intensive care unit (NICU) of Alzahra Hospital in Isfahan, Iran. Methods: In this cross-sectional study, the population consisted of all neonates who were admitted to the NICU of Al-Zahra Hospital in Isfahan, Iran, from April 2017 to March 2018. Neonates who had a positive culture (blood, cerebrospinal fluid, urine, eye discharge, and tracheal tube secretions) were enrolled. The data were collected by a structured questionnaire, including maternal and neonatal information. Results: In this study, 56 newborns admitted to the NICU of Alzahra Hospital in Isfahan were studied. Their age range was within 5-28 days (18.88±8.41). Thirty-two (57.1%) neonates were male, and 24 (42.9%) newborns were female. In total, 26 (46.4%) neonates had prematurity that was the most common reason for hospitalization. The most isolated microorganisms were Staphylococcus epidermidis, Enterococcus, Klebsiella, Enterobacteriaceae, Candida spp., Acinetobacter, Streptococcus pneumoniae, E. coli, and Streptococcus viridans, respectively. Conclusion: According to the results of this study, the frequency of nosocomial infections in the NICU of Alzahra Hospital in Isfahan was 7.4%. The findings of this study highlighted the importance of paying more attention to controlling and preventing hospital infections in NICUs.